It was another skin: The kitchen as home for Australian post-war immigrant women - Supski, Sian (Taylor & Francis, 2006)
This article examines the importance of the kitchen for immigrant women who arrived in Australia in the late 1940s and 1950s. Using oral history interviews with 27 immigrant women I examine the multiple and overlapping ways in which they 'make' home. Women construct home through the kitchen by re/negotiating the kitchen space to ensure that the kitchen and their central placement within it produces a 'feeling' of being 'at home'. Women shape the architecture and design of the kitchen in terms of their own understandings of the discourses of efficiency and domesticity, and also through colour and decoration, to 'make' the kitchen home. These understandings will be explored through nuanced readings of the immigrant women's stories of their kitchen lives.